2020
DOI: 10.1016/j.patrec.2018.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Local-global nested graph kernels using nested complexity traces

Abstract: In this paper, we propose two novel local-global nested graph kernels, namely the nested aligned kernel and the nested reproducing kernel, drawing on depth-based complexity traces. Both of the nested kernels gauge the nested depth complexity trace through a family of K-layer expansion subgraphs rooted at the centroid vertex, i.e., the vertex with minimum shortest path length variance to the remaining vertices. Specifically, for a pair of graphs, we commence by computing the centroid depth-based complexity trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Remarks: The dynamic time warping based global alignment kernel k GA has been proven to be a powerful tool of analyzing vectorial time series [33]. To extend the effective kernel k GA for time series analysis domain into the graph kernel domain, Bai et al [34] have developed a family of nested graph kernels through k GA . Specifically, they commenced by decomposing each graph structure into a family of K-layer expansion subgraphs rooted at the centroid vertex.…”
Section: B the Dynamic Time Warping Frameworkmentioning
confidence: 99%
“…Remarks: The dynamic time warping based global alignment kernel k GA has been proven to be a powerful tool of analyzing vectorial time series [33]. To extend the effective kernel k GA for time series analysis domain into the graph kernel domain, Bai et al [34] have developed a family of nested graph kernels through k GA . Specifically, they commenced by decomposing each graph structure into a family of K-layer expansion subgraphs rooted at the centroid vertex.…”
Section: B the Dynamic Time Warping Frameworkmentioning
confidence: 99%
“…Given a set of graphs G, for each sample graph Gp ∈ G: (1) we compute the K-dimensional DB representation DB K p;v rooted at each vertex (e.g., vertex v 2 of Gp). We represent this as a K-dimensional vertex vector, where each element Hs(G K p;2 ) of DB K p;v represents the Shannon entropy of the K-layer expansion subgraph rooted at v 2 [32].…”
Section: Align Tomentioning
confidence: 99%
“…To construct reliable correspondence information for the graphs, in this work we employ a depth-based (DB) representation [32] as the initial vectorial vertex representations (i.e.R K ). This is because the DB representation of each vertex is computed by measuring the entropies on a family of k-layer expansion subgraphs rooted at the vertex, where the parameter k varies from 1 to K. It has been shown that such a Kdimensional DB representation can be viewed as a nested vertex representation that encapsulates a rich nested entropybased information content flow from each local vertex to the global graph structure, as a function of depth.…”
Section: Align Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure of computing the correspondence matrix. Given a set of graphs, for each graph Gp: (1) we compute the K-dimensional depth-based (DB) representation DB K p;v rooted at each vertex (e.g., vertex 2) as the K-dimensional vectorial vertex representation, where each element Hs(G K p;2 ) represents the Shannon entropy of the K-layer expansion subgraph rooted at vertex v 2 of Gp[35]; (2) we identify a family of K-dimensional prototype representations PR K = {µ K 1 , . .…”
mentioning
confidence: 99%